Effect of processing techniques on energy content and amino acid digestibility in corn germ meal fed to growing pigs - Jinbiao Zhao; Zhaoyu Liu; Xiaoming Song; Meiyu Yang; Zhongchao Li; Ling Liu (Animal Bioscience)
Objective The study was conducted to determine energy contents, apparent total tract digestibility (ATTD) of nutrients, the apparent (AID) and standardized (SID) ileal digestibility of amino acids (AA) in corn germ meals (CGM) produced by processing technologies of wet milling (CGM-CV1 and CGM-CV2), heating-dried CGM with steep liquor (CGMSL-DH) and dried using indirect heat (CGMSL-IH), corn germ expellers (CGE) and dry-grind processing method (CGM-DG). Methods In Exp. 1, forty-two crossbred male barrows with an initial body weight (BW) of 51.2±4.5 kg were assigned to 1 of 7 diets in a randomized complete block design. In Exp. 2, seven cannulating barrows with an initial BW of 35.3±1.3 kg were assigned to 7 diets in each period according to a Latin square design. Each diet included 6 replicates. Results The ATTD of acid detergent fiber and gross energy (GE), and SID of most AA, except for tryptophan (Trp) and cysteine (Cys), in CGMSL-IH was greater (p<0.05) than those in CGM-CV2. The ATTD of organic matter (OM), crude protein and GE, and SID of most AA, except for arginine (Arg), histidine (His), lysine (Lys) and tyrosine (Tyr), in CGMSL-DH was greater (p<0.05) than those in CGM-CV1 for pigs. The ATTD of GE and acid-hydrolyzed ether extract, contents of digestible and metabolizable energy (ME), and SID of AA, except for Arg, His, Lys, Phenylalanine, Trp, Cys, glutamic acid, glycine and Tyr, in CGE were greater (p<0.05) than those in CGM-CV1. The ATTD of OM and GE, and SID of all AA in CGM-DG were greater (p<0.05) than those in CGM-CV1. Compared with the CGM-CV1, CGM-CV2 showed a greater (p<0.05) ATTD of GE and SID of some AA for growing pigs. Conclusion Different processing technologies lead to large variations in energy contents and AA digestibility of CGM for growing pigs. The CGE contains more available energy compared with CBM-CV1, and CGMSL-DH, CGMSL-IH and CGM-DG provides more ileal digestibility of AA for growing pigs compared with the CGM-CV1 and CGM-CV2.